Intervenção Assistida por Animais com crianças hospitalizadas: efeitos nas condutas comunicativas, sinais vitais e níveis de cortisol - Oliveira, Glícia Ribeiro de (2018)
INTRODUCTION: This study is aligned with the researches that show that the animal-assisted intervention (AAI) is a possibility to mitigate the possible vulnerability of children when hospitalized and that the presence of a dog contributes to face it, in addition to enhance a sense of well-being. Two complementary studies are presented. PURPOSE: Study 1: To describe comparatively the communicative behavior of children hospitalized with (AAI) and without a dog, in a playful context. Study 2: To describe comparatively the vital signs results and of the cortisol levels in children hospitalized, pre- and post-animal assisted Intervention. METHODS: Study 1: 46 subjects participated in a leisure activity (reading a children's book): 27 in the presence of a dog (Research Group-RG-AAI) and 19 subject without the dog (Control Group-CG). The activity was conducted individually and spontaneously, using the proposal of a ‘Velcometry’, in which the subject would interact with the figures on the book with Velcro straps on the back of the book, on the dog vest (RG), or in the felt board (CG). Collected data were submitted to descriptive and comparative analysis from the analysis of the videos of the RG and CG by the researcher and by 04 judges (02 specialized in the AAI performance and 02 speech-language pathologists). Categories (and their subcategories) of relevant content were established. For the RG and the CG: Non-verbal behavior (body posture; visual contact; facial expression); Interaction and dialogic activity; Motivation for reading. Specifically for the RG: Spontaneous autobiographical reports and photographic records of the AAI. Study 2: 27 subjects participated in a leisure activity (reading a children's book) in the presence of a dog (AAI): The vital signs were measured and material (saliva) was collected to assess the cortisol level before and after the AAI. The collected data were compared from the analysis of the vital signs and cortisol results, before and after the AAI. RESULTS: Study 1: The RG was highlighted in the sample studied: gradual increase of visual and body contacts with the researcher and with the dog in the course of the activity; significant occurrence of happy facial expressions, interaction and dialogy; as well as of spontaneous narratives and motivation for reading. Study 2: In subjects studied, in pre- and post-AAI contexts, vital signs did not show statistically significant differences; however, the reduction of cortisol levels was statistically significant and it was associated to the immune responses on the reduction of stress. CONCLUSION: Study 1: The AAI provided beneficial effects, establishing itself as powerful international resource to address the biopsychic burden involved in the hospitalization process of the child. Study 2: The AAI can mitigate the effects of the stressful environment and enhance the sense of well-being of children hospitalized